2008
DOI: 10.1017/s1751731107001097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild heat stress and mild infection pressure on immune responses to an E. coli infection in chickens

Abstract: Outdoor or organic farming demands robust chickens that are able to combat common infections before they spread to the flock. Priming the immune system of the chickens early in life with micro-organisms that they will encounter later in life prepares chickens to a life in environments where they are subjected to a more natural level of infection pressure. Also, exposure to non-infectious stressful situations may prepare the immune system to combat infectious challenges. The present study investigated whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(24 reference statements)
0
9
0
1
Order By: Relevance
“…It has been suggested that exposition to non-infectious stressful situations might prepare the immune system to fight against infectious challenges [ 16 , 17 ] and protection mediated by heat shock proteins against inflammatory and infectious processes occurs due to the suppression of inflammatory mediators [ 23 ]. Indeed, lower stress response with reduction in the levels of corticosterone has been reported in three-old-chicks previously treated with heat between D16 and D18 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that exposition to non-infectious stressful situations might prepare the immune system to fight against infectious challenges [ 16 , 17 ] and protection mediated by heat shock proteins against inflammatory and infectious processes occurs due to the suppression of inflammatory mediators [ 23 ]. Indeed, lower stress response with reduction in the levels of corticosterone has been reported in three-old-chicks previously treated with heat between D16 and D18 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the stress response is non-specific, thermotolerance induction might also improve resistance to other kinds of stresses. In fact, non-infectious stress situations may prepare the immune system to fight against infectious challenges [ 16 , 17 ]. Although the consequences of thermal manipulation during incubation on the performance and meat quality of broiler chickens have been widely assessed, the responses of birds to other types of stresses have not been addressed to date.…”
Section: Introductionmentioning
confidence: 99%
“…When the immune system is activated, there are physiological and metabolic changes in their organism, which alter food intake and consequently weight gain and feed conversion ratio. In commercial broiler breeding, environmental stress factors such as overcrowding, humidity, low quality of the air and the presence of infectious and stressing agents may alter their metabolism and nutrient absorption (Norup et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which heat stress modulates immunity is in part due to the extent of induction of heat shock proteins in lymphocytes, heterophils, and macrophages [77], while cold stress suppresses plasma corticosterone levels and enhances thyroid hormone levels [81]. Even mild heat stress can cause a redistribution of lymphocytes and immune system changes, although these changes may have minimal impact on resistance to some disease challenges [82].…”
Section: Temperature Stressorsmentioning
confidence: 99%